ANGGARAN MENSEJAHTERAKAN : PROBLEM DALAM FORMULASI - Ria Angin (Metafora: Education, Social Sciences and Humanities Journal, 2020)
Target of local government budget2014 in Jember is to achieve an increase in the human development index (HDI) approached the national of human development index (NHDI). As anaccelerationsteptoachievethisgoal,the Jember Regency set the bupati regulation of JemberRegency No. 26 of 2013. This effort was obstacled because (1) the limited capacity of the human resources (HR) in the understanding of gender issues, (3) Still has disaggregated data on level base line, (5) There are no maximal network data and information on research related to gender responsive budgeting, (7) There is no method as well as monitoring and evaluation tools that can not be implemented optimally. Nevertheless the potential to realize the public welfare budget is still possible because of the strong goodwill of stakeholders.